Mafic Minerals in the South Pole‐Aitken Basin. Issue 6 (20th June 2019) - Zhang, Xunyu; Zhu, Meng‐Hua; Bugiolacchi, Roberto
Abstract: The formation of the South Pole‐Aitken (SPA) basin is thought to excavate the deep crust or mantle because of its large size. The pervasive orthopyroxene‐dominated materials found across the basin suggest that they either represent the SPA impact melt or the excavated materials from the lower crust and/or upper mantle. This study analyzes the relative content and distribution of mafic minerals in the SPA area based on the spectra from small fresh craters. The orthopyroxene‐dominated materials in the nonmare regions are classified into two types based on their distribution and different composition. One is distributed from the center to the edge across the SPA basin and interpreted as the SPA impact melt. The other is Mg richer and generally located in some plagioclase‐rich regions (e.g., some large impact craters/basins and the SPA edge), thought to represent materials from the lower crust and/or upper mantle. For the maria in the SPA area, the basaltic materials in the northwest are found to be richer in olivine and/or clinopyroxene than the southern ones. Plain Language Summary: The South Pole‐Aitken (SPA) basin is the largest impact structure on the farside of the Moon, which is believed to excavate and melt rocks from deep beneath the lunar surface due to its large size. However, the melted rocks and excavated rocks are difficult to be distinguished because of their similar composition. This study analyzes the composition of fresh materials exposed by small impact craters in the SPA basin, which enhances the diagnostic features of the data acquired by orbital instruments. A geostatistical method is also applied to enhance the variation trend of diagnostic features in different locations. The melted rocks and excavated rocks in the SPA basin are distinguished based on their distribution and relatively different composition. The melted rocks are widely distributed across the basin from the center to the edge. In contrast, the excavated rocks are generally located in some specific regions. Key Points: Two types of orthopyroxene‐dominated materials in the South Pole‐Aitken basin were distinguished One, widely distributed from center to edge across the basin, is interpreted as the South Pole‐Aitken impact melt The other with lower calcium, distributed in some feldspathic regions, is considered the excavated deep‐seated material